Cross-linked structures reinforced the bamboo fiber/poly(lactic acid) composites with high heat resistance and their environmental impact through the life cycle assessment analysis - Chen, Hui; Chen, Pengrui; Qi, Zhongyu; Sun, Ce (Frontiers in Materials, 2024)
In order to prepare low-cost and heat-resistant poly(lactic acid) (PLA) composites, in this study, bamboo fiber (BF) was added to stereo-complex crystal PLA (SC-PLA) to prepare heat-resistant composites. Poly[(phenyl isocyanate)-co-formaldehyde] [a polyaryl polymethylene isocyanate (PAPI)] was used to form cross-linked structures between SC-PLA and BF, and the effects of PAPI-cross-linked structures on the crystallization properties, mechanical properties, and heat resistance of BF/SC-PLA composites with different BF contents were systematically investigated. When 15% BF was added, the mechanical properties of the composite were significantly improved. The tensile strength increased by 85.5% compared to the unmodified composite, reaching 34.7 MPa, which was even higher than that of the SC-PLA composite (33.1 MPa). In addition, in order to explore the impact of the PAPI-modified BF/SC-PLA composite on the environment and carbon emissions, a life cycle assessment (LCA) of the composites was conducted. The addition of BF effectively reduced the impact of the composite on the environment. Notably, the emissions of CO2 decreased by approximately 11.7%, and the freshwater, marine, and land ecotoxicity were also significantly reduced. This work provided a reference for the preparation of low-cost and heat-resistant PLA composites for heat-resistant food packaging and disposable tableware and expanded the application of PLA products in the field of heat-resistant materials.